INTERNET OF THINGS (IOT) APPLIED IN CONSTRUCTION INDUSTRY: A SYSTEMATIC REVIEW - Silva dos Santos, Rodrigo; Assayag, Elias Simão (International Journal of Engineering Technologies and Management Research, 2022)
The Internet of things (IoT) involves several internet-connected devices that interact with each other to learn and share information between humans and machines and between machines and machines, making the related processes more comprehensive, innovative, simple, and efficient. There are several applications of IoT in construction, such as using computational tools in structural design, georeferencing, construction management, and using technological tools in construction sites. Therefore, this article presents a systematic review of the most relevant studies from Industry 4.0 and the application of IoT in the construction industry to present the impacts these technologies can promote in construction. On this, the 4.0 technology implementation and their construction innovations can improve work conditions through innovative tools, machines, and devices, increasing productivity and reducing production costs. Therefore, drone operation is one of the most used construction technologies, mainly because the costs are low for construction companies and their owners. However, technologies such as BIM and robotics are widely used.